DECONSTRUCTION, APORIA AND THE IMPOSSIBILITY OF JUDGEMENT - Audronė Žukauskaitė (Problemos)
Deconstruction can be defined as a philosophical project which in the process of interpretation seeks to reveal contradictory or undecidable values within the philosophical text. Usually a contradiction occurs between incompatible meanings of the same term, between different functions of the proposition (constative and performative), between declared propositions and unconsciuos presuppositions of the same text. This experience of undecidability comes from the Greek, aporos, which means "without passage", "without issue". Aporia implies the suspension of judgement; on the other hand, no judgement is possible without the experience of aporia. This "aporethical logic" means that the conditions of possibility of judgement designate simul-taneously the conditions of its impossibility. For example, postmodern ethics can be described as the annulment of ethical judgement: every attempt to make ethical decision is violent as long as it is regulated by normative and universal system; on the contrary, the refusal to define ethical relation as ethical already means ethical position. The aporia of ethics is also the aporia of time: ethical judgement as possibility is projected towards the future or as impossibility remains in the past. Derrida’s example of gift demonstrates that ethical judgement does not appear as ethical in present moment. Postmodern theories of politics also provide an example of the impossibility of political judgement. The political field is interpreted throuhg the aporia of law: the universal and unattainable law is inconceivable to singular, finit individual; but if it is idiomatic it ceases being the law. The aporia of law is also the aporia of time: the present of the law is always missing. The impossibility of judgement suspends violence and predicts "lesser violence": in this way the impossibility of politics is the condition of its possibility.